The Araliaceae of Thailand - Esser, Hans-Joachim; Jeeb, Matthew H. P. (Thai Forest Bulletin (Botany), 2014)
A revision of Araliaceae for the Flora of Thailand has recently been completed. 53 species in 12 genera were recognized. There are six species endemic to Thailand. Two new species were found during the studies, and three new records for Thailand. Seven new synonyms were proposed. Keys to the genera are provided in this paper. Several of the genera are discussed briefly, and a few open taxonomic problems mentioned.